Active Dual-Wavelength Optical Switch-Based Plasmonic Demultiplexer Using Metal-Kerr Nonlinear Material-Metal Waveguide - Yan Kong; Rong Lin; Wenchao Qian; Qi Wei; Cheng Liu; Shouyu Wang (IEEE Photonics Journal)
To realize active light control with a compact structure, a nanoscale optical switch-based plasmonic demultiplexer is proposed. The device is designed according to the metal-Kerr nonlinear material-metal waveguide with multiple resonant cavities, providing the capability of active optical regulation for dual wavelengths: Signals of $\text{1310}$ and $\text{1550 nm}$ can be guided into either output with high directional extinction ratios larger than 30 dB controlled by another pump light of ${\text{730 nm}}$ with low power. Considering its light control capability and compact configuration, it is believed that the proposed demultiplexer can be adopted in the future logic plasmonic circuits.